Pengaruh Kondisi Keuangan Terhadap Pemberian Opini Audit Going Concern Dengan Auditor Bereputasi Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022) - Febriati, Ervina; Achmad, Komarudin (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to examine the effect of financial conditions on providing going concern audit opinion with reputable auditors as the moderating variable. The secondary data—from 93 samples of infrastructure companies listed on the Indonesia Stock Exchange from 2020-2022 selected through purposive sampling—are collected from the Indonesia Stock Exchange official website. The results of the logistic regression analysis exhibit that financial condition has a negative effect on the going concern audit opinion; and reputable auditor is unable to moderate the effect of financial condition on going concern audit opinion. The results of the study suggest that auditors consider financial conditions in providing a going concern audit opinion.